Enhancing creative arts teaching and learning through a blended learning approach: teachers’ perspectives - Hlatshwayo, Bongiwe (My University, 2024)
ICT in education has changed the way people teach and learn. This transformation has provided education systems with new ways to make education available in various learning platforms. Blended learning is defined as an educational approach that combines face-to-face and online learning with the use of technology. This educational approach gives learners the opportunity to learn via online media as well as through traditional face-to-face. During the covid-19 pandemic, the incorporation of blended learning in many South African schools became imperative in order to allow learners and teachers to recover lost teaching and learning time due to hard lockdown imposed by the government. Teachers were pressured to quickly acquire technological devices and sharpen their ICT skills in order to implement blended learning in their classrooms. The purpose of this study was to investigate ways in which blended learning can be adopted in South African schools to enhance Creative Arts teaching and learning. This qualitative study was conducted in three schools in Gauteng province, and it explored the experiences of Creative Arts teachers who have attempted to use blended learning in their practice. Interviews were used to collect data and data analysis was conducted thematically. According to the findings of this study, blended learning provides learners with modern technological experience which is essential in this digital age. However, the rapid adoption of blended learning in South African schools did not coincide with the process of preparing teachers to successfully implement this educational approach. A number of South African schools struggled to successfully implement blended learning due to a lack of ICT professional development, technical resources, and technical support. According to the study, there is a need to establish an effective ICT professional development program in South Africa, that will provide teachers with the necessary skills and knowledge to effectively incorporate blended learning into their practice.
A research report submitted in partial fulfilment of the requirements for the degree Master of Education to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2023
Keywords: Blended learning; Digital tools; Professional development